A new south polar Digital Terrain Model of Mars from the High-Resolution Stereo Camera (HRSC) onboard the ESA Mars Express - Putri, ARD; Sidiropoulos, P; Muller, JP; Walter, SHG; Michael, GG (Elsevier, 2019)
The first high-resolution Digital Terrain Model (DTM) of the entire South Pole of Mars has been produced. A modified version (Kim and Muller, 2009) of a NASA-VICAR-based pipeline developed by DLR (German Aerospace Centre) and JPL (Jet Propulsion Laboratory) has been employed with image matching based on the Gotcha (Gruen-Otto-Chau) algorithm (Shin and Muller, 2012) with a specialised setup for the polar region. DTM products have been produced with more than twice the resolution (50 m/pixel) of the gridded Mars Orbiter Laser Altimeter (MOLA) 512 pixels/degree (112 m/pixel) over the South Polar Residual Cap (SPRC) and the Mars South Polar region (82° - 90° S) in MOLA and areoid reference. The accuracy of the HRSC orbital DTMs are compared against a MOLA reference with good results. HRSC orthorectified strip images from 12.5 to 50 m have also been produced from the base DTMs and these have been processed into a 12.5 m mosaic. HRSC strip products are currently being assessed as base images for automatic co-registration of thousands of high-resolution images, making them geometrically consistent with the surface conditions imaged by HRSC. In some cases, Context Camera (CTX) DTMs have been automatically produced and co-registered to the HRSC image strips and these, in turn, are being employed for automated co-registration of higher-resolution images.